A systematic approach towards optimization of brackish groundwater treatment using nanofiltration (NF) and reverse osmosis (RO) hybrid membrane filtration system. (September 2022) - Srivastava, Alka; Singh, Rajneesh; Rajput, Vishnu D.; Minkina, Tatiana; Agarwal, Smriti; Garg, Manoj Chandra
Abstract: This research compares the performance efficiencies of Nanofiltration (NF), Reverse osmosis (RO), and Nanofiltration-Reverse Osmosis (NF-RO) hybrid membrane filtration systems, for treatment of brackish groundwater in Delhi-NCR region. Central composite design (CCD) of response surface methodology (RSM) were applied to formulate predictive models for the optimization and simulation of various responses, viz . Water flux, salt rejection, permeate recovery and specific energy consumption (SEC). Three different input factors (feed concentration, pH and pressure) were evaluated. Significance of RSM model was tested and validated with use of an analysis of variance (ANOVA). The models were also compared graphically for their prediction ability. The optimum conditions were determined by numerical optimization of the NF and RO membrane pilot plants. Finally, hybrid configurations of NF and RO were investigated utilising the optimum conditions to identify the technology suitable for the remediation of brackish groundwater. Despite, RO membrane eliminating over 99% of TDS from groundwater, the lower recovery rate renders it environmentally unfavourable. Result indicates that recovery of the hybrid system (40.35%) was greater than that of RO alone (18.796%) and SEC also decreases (5.090–3.8 kW H/m 3 ). Hence, combining a hybrid membrane arrangement with NF-RO to treat brackish groundwater for improved recovery and lower SEC is a viable alternative. Graphical abstract: Image 1 Highlights: Combination of NF-RO for the treatment of brackish water. Performance efficiencies by using pilot-scale NF, RO, and hybrid NF-RO filtration system. Rejection, Recovery and Specific Energy Consumption (SEC) studies. Optimization studies through response surface methodology (RSM). Recovery of the hybrid system is four times greater than that of the RO alone.